(untitled) (Bangladesh Journal of Child Health, 2017)
Background: Liver is prone to different diseases including congenital, infections, metabolic and malignancies. Liver biopsy is an aggressive but definitive way to diagnose liver diseases. Objective: To diagnose different types of liver diseases and to determine the safety of percutaneous liver biopsy by disposable Tru-Cut needle. Materials & Methods: A descriptive study was done in the department of Pediatric Gastroenterology, Hepatology & Nutrition, Dhaka Shishu (Children) Hospital, Dhaka, Bangladesh from January 2014 to January 2016. After getting history, physical examination and ultrasonogram, the biopsy was done with the help of Tru-Cut needle of different sizes under local anesthetics (2% lidocaine) with 3 hours fasting. The biopsy specimens were immediately fixed in 10% formal-saline and alcohol. The tissues were processed in automatic tissue processor under standard condition. Results: Age of the children was 1 month to 12 years with mean age of 3.1 years (3.1±0.763) with a range from 1 month to 12 years and male:female ratio was 1.1:1. The most common histological diagnosis was neonatal hepatitis (23.3%) followed by biliary atresia (16.7%). There were chronic hepatitis (10.0%), glycogen storage disease (10.0%), cirrhosis (6.7%) and hepatoblastoma (6.7%) in moderate frequency. Other cases of least frequency (3.3%) were fatty change, lipid storage disease, intra-hepatic bile duct paucity, congenital hepatic fibrosis and Von Meyenburg complex. Neonatal hepatitis & biliary atresia were common among ?1 year age group and glycogen storage disease, hepatoblastoma & non-specific changes in 1-5 year age group. In the older children (>5 years), chronic hepatitis (10.0%) & cirrhosis (6.6%) were the common causes. Consanguinity was present in storage disease, neonatal hepatitis, congenital hepatic fibrosis, von meyenburg complex and intra-hepatic bile duct paucity. After biopsy, mild pain and discomfort was present in 23 (38.3%) children, while diffuse pain which required analgesics in 11 (18.3%) children without any major complications. Conclusion: Liver biopsy is a useful and practical tool for the diagnosis of pediatric liver diseases. Neonatal hepatitis, biliary atresia, storage disorders and chronic hepatitis were common entities in our set up. Consanguinity was more common in hereditary and metabolic liver diseases. Liver biopsy is safe having minimal complications. Bangladesh J Child Health 2016; VOL 40 (2) :72-78